Evaluasi Layanan Data Center di Dinas Komunikasi dan Informatika Kota Batu dengan Menggunakan ITIL V.3 Framework Sub Domain Common Service Operation dan Organizing Service Operation - Dian Herbayu; Yusi Tyroni Mursityo; Aditya Rachmadi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Batu City Informatics Communication Office is one of the government agencies responsible for the implementation of E-Government-based public services and information management. DISKOMINFO Kota Batu provides services in the form of data centers. The form of data center services to Batu City agencies includes requests for website subdomains. Operational problems that are experienced include the absence of routine and scheduled data backups. The common focus is management's commitment to improve service quality. To find out the form of service management carried out by the Ministry of Communication and Information, it is necessary to evaluate the maturity level of data center services. The current condition of the data center does not meet standards and the management therein is not carried out regularly. Maturity level evaluation using the ITIL Framework with the Service operation domain. This evaluation produces recommendations for data center service management. During the evaluation process, valid data were collected by means of document studies, interviews, and questionnaires to obtain a maturity level analysis of the Service operation domain in the Common Service operation Activities sub domain of 2.1 (repeatable). and the organizing service operation of 1.9 (initial). This analysis shows that there are still many data center service management processes that have not been implemented as well as service management functions. The existence of recommendations from this evaluation will assist the Ministry of Communication and Information in improving the management of standardized data center services.